A One-Step Dual-Mode Aptasensor for Subnanomolar Detection of Lead Ions Based on Electrochemiluminescence and Fast Scan Voltammetry. Issue 12 (25th August 2020) - Hao, Tingting; Zhang, Chunfeng; Lin, Han; Wei, Wenting; Yang, Fan; Wu, Yangbo; Niu, Lingmei; Kang, Weijun; Guo, Zhiyong
Abstract : Herein, a dual-mode aptasensor for subnanomolar detection of lead ions Pb 2+ based on electrochemiluminescence (ECL) and fast scan voltammetry (FSV) was developed. It could be one-step fabricated using an all-in-one probe Fe3 O4 @Au-ssDNA&Ru-NH2 which has multiple functions: Fe3 O4 core achieves one-step preparation of the aptasensor; Au shell provides a place for assembly and electrochemical reactions; ssDNA can selectively recognize and capture target Pb 2+, and ferrocene labeled on it could provide fast scan voltammetric signal and participate in changes of ECL signals; and Ru-NH2 is a signal marker for ECL detection. In presence of target Pb 2+, ssDNA folds to form G-quadruplex, and ferrocene labeled on its end approaches to the Au shell surface resulting in easier electron transfer. So the electrochemical signal is enhanced, and ECL quenching occurs. Electrochemical peak current increased about 1000 times at 100 V s −1 using FSV, making its sensitivity compatible with that of ECL to obtain highly sensitive dual-mode detection. Pb 2+ could be detected in the concentration range from 10 −10 mol l −1 to 10 −6 mol l −1 with a limit of quantitation (LOQ) 10 −10 mol l −1 . Selectivity, stability, reproducibility, accuracy and practicality are good. This extremely simple method provides a valuable idea for developing biosensors for field detection applications.